2002
DOI: 10.1105/tpc.001263
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the IRT1 Metal Transporter Is Controlled by Metals at the Levels of Transcript and Protein Accumulation

Abstract: Iron, an essential nutrient, is not readily available to plants because of its low solubility. In addition, iron is toxic in excess, catalyzing the formation of hydroxyl radicals that can damage cellular constituents. Consequently, plants must carefully regulate iron uptake so that iron homeostasis is maintained. The Arabidopsis IRT1 gene is the major transporter responsible for high-affinity iron uptake from the soil. Here, we show that the steady state level of IRT1 mRNA was induced within 24 h after transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
556
6
9

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 667 publications
(600 citation statements)
references
References 44 publications
(57 reference statements)
29
556
6
9
Order By: Relevance
“…Hence, Cd addition reduced the shoot fresh and dry weight also have been studied previously in different plant species such as wheat (Mane et al, 2010) and barley (Zaltauskaite and Sliumpaite, 2013). Cadmium may impede with nutrient uptake due to competition for the same transmembrane carriers, thereby leading to the altered tissue nutrient contents (Connolly et al, 2002). These interactions between Cd and other essential nutrients may lead to physiological disarrays as well as a reduction in growth (ElBeltagi et al, 2010).…”
Section: Introductionmentioning
confidence: 71%
“…Hence, Cd addition reduced the shoot fresh and dry weight also have been studied previously in different plant species such as wheat (Mane et al, 2010) and barley (Zaltauskaite and Sliumpaite, 2013). Cadmium may impede with nutrient uptake due to competition for the same transmembrane carriers, thereby leading to the altered tissue nutrient contents (Connolly et al, 2002). These interactions between Cd and other essential nutrients may lead to physiological disarrays as well as a reduction in growth (ElBeltagi et al, 2010).…”
Section: Introductionmentioning
confidence: 71%
“…To evaluate the biological significance of such a regulatory mechanism, we determined the timing of FIT post-transcriptional regulation visualized by the decrease in constitutively expressed FIT-GFP in Col/35S::FIT-GFP plants, compared with other known responses to iron starvation. The most commonly used and robust marker for the establishment of these early molecular responses is the accumulation of IRT1 protein in roots (Connolly et al, 2002). Time-course analyses of protein accumulation by western blot revealed that in our conditions, IRT1 protein starts to accumulate 24-48 h after transfer to iron-limiting conditions, and keeps increasing until day 5 (Figure 3a).…”
Section: Fit Post-transcriptional Control Is Synchronized With Earlymentioning
confidence: 86%
“…However, the IRT1 protein is not specific for iron. Other metals such as Zn 2+ , Mn 2+ and Co 2+ can be transported into plants via the IRT1 protein in Arabidopsis (Eide et al, 1996;Korshunova et al, 1999;Connolly et al, 2002;Henriques et al, 2002;Varotto et al, 2002;Vert et al, 2002). Following transportation into root cells, iron is chelated by citrate or nicotianamine and distributed to the shoots (Stephan and Scholz, 1993;Briat et al, 2007).…”
Section: Introductionmentioning
confidence: 99%